1995
DOI: 10.1111/j.1442-2042.1995.tb00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nephrectomy Using a Retroperitoneal Approach: Comparison With a Transabdominal Approach

Abstract: To evaluate the efficacy of the retroperitoneal approach in laparoscopic nephrectomy, our procedures involving laparoscopic nephrectomy using a retroperitoneal approach are described and the clinical results of six patients treated in this way are compared with those of 32 transabdominally nephrectomized patients. Of the six retroperitoneally nephrectomized patients, six kidneys were successfully removed without severe complication, and 28 kidneys were successfully removed in the 32 intraabdominally approached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…The retroperitoneal approach was subsequently developed by Gaur and coworkers 11 and has been used by several investigators. 6,[12][13][14] Because the kidney is in the retroperitoneal space, the retroperitoneal approach may decrease the operative time by 20 to 30 minutes compared with the transperitoneal approach. 6,15 An additional advantage of retroperitoneoscopic nephrectomy over the conventional transperitoneal approach is ligation of the renal vessels prior to dissection of the kidney, which is important for preventing hematologic spread of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retroperitoneal approach was subsequently developed by Gaur and coworkers 11 and has been used by several investigators. 6,[12][13][14] Because the kidney is in the retroperitoneal space, the retroperitoneal approach may decrease the operative time by 20 to 30 minutes compared with the transperitoneal approach. 6,15 An additional advantage of retroperitoneoscopic nephrectomy over the conventional transperitoneal approach is ligation of the renal vessels prior to dissection of the kidney, which is important for preventing hematologic spread of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy and minimally invasive nature of laparoscopic nephrectomy has been extensively discussed. [1][2][3][4][5][6][11][12][13][14][15] Because our cases were patients with CRF maintained on hemodialysis, the main factor affecting the duration of the hospital stay may not be their postoperative course but the management of their dialysis or treatment of disorders associated with renal insufficiency. Therefore, in order to evaluate the invasiveness of the present procedure, we utilized factors that estimate the catabolic status of patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al compared six RPNs with 32 TPNs and found a shorter operative time and less blood loss with RPN. 32 There were three conversions in the TPN group and none in the RPN group. Further comparisons by Guillonneau et al 33 and McDougall and Clayman 34 revealed similar blood loss, complication rates and hospital stay between RPN and TPN.…”
Section: Retroperitoneoscopic Versus Transperitoneal Laparoscopic Nephrectomymentioning
confidence: 94%
“…It avoids the risk of injury to intra-abdominal organs and enables quicker recovery [11]. It also facilitates easy positioning of the patient and direct access to the kidney, resulting in a faster operation [12,13]. The kidney falls anteriomedially with gravity, exposing the hilum with minimal dissection and retraction.…”
Section: Discussionmentioning
confidence: 99%